1986
DOI: 10.1113/jphysiol.1986.sp016347
|View full text |Cite
|
Sign up to set email alerts
|

Calcium dependence of presynaptic calcium current and post‐synaptic response at the squid giant synapse.

Abstract: SUMMARY1. Neurotransmitter release has a non-linear dependence upon the external Ca concentration, [Ca].. This may be due to a 'co-operative' action of Ca in triggering release. The dependence of presynaptic Ca currents and post-synaptic currents (p.s.c.s) upon [Ca]. was examined at voltage-clamped 'giant' synapses of squid to determine whether this 'co-operativity' occurs during or after influx of Ca into the presynaptic terminal.2. Presynaptic Ca current was proportional to ([Ca]./(1 + [Ca]O/KD))n, where n, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
128
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(138 citation statements)
references
References 48 publications
8
128
2
Order By: Relevance
“…This suggests that the amplitude of a presynaptic Ca transient may well reflect the presynaptic Ca influx, and hence the average presynaptic Ca current. Our finding that the slope of the field EPSP is a power function of Ca influx is in agreement with previous experiments performed in the squid giant synapse (Augustine et al, 1985b;Augustine and Charlton, 1986). The power relationship between the slope of the field EPSP and the amplitude of the Ca transient in our experiments is consistent with the finding that the EPSP amplitude is nonlinearly related to the presynaptic Ca accumulation induced by tetanic stimulation at crayfish neuromuscular junction (Zucker et al,199 1).…”
Section: Ca Indicator Loading Techniquesupporting
confidence: 82%
See 1 more Smart Citation
“…This suggests that the amplitude of a presynaptic Ca transient may well reflect the presynaptic Ca influx, and hence the average presynaptic Ca current. Our finding that the slope of the field EPSP is a power function of Ca influx is in agreement with previous experiments performed in the squid giant synapse (Augustine et al, 1985b;Augustine and Charlton, 1986). The power relationship between the slope of the field EPSP and the amplitude of the Ca transient in our experiments is consistent with the finding that the EPSP amplitude is nonlinearly related to the presynaptic Ca accumulation induced by tetanic stimulation at crayfish neuromuscular junction (Zucker et al,199 1).…”
Section: Ca Indicator Loading Techniquesupporting
confidence: 82%
“…Two-electrode voltage-clamp studies of the squid giant synapse have shown that the postsynaptic potential has a relatively linear dependence on the presynaptic Ca current, approximating a first-to secondpower function (Llinas et al, 1976, 198 1;Augustine and Eckert, 1984). However, with a three-electrode voltage-clamp technique, which provides a more accurate measurement of presynaptic Ca current, Augustine and colleagues (Augustine et al, 1985b;Augustine and Charlton, 1986) found that the relationship between presynaptic Ca current and postsynaptic potential follows a third-power function in the squid giant synapse. The latter finding suggests that the "cooperative" action of Ca takes place at the step or steps beyond the entry of Ca into the presynaptic terminals.…”
mentioning
confidence: 99%
“…Furthermore, the high-affinity site would contribute to the Ca 2ϩ cooperativity of transmitter release defined experimentally. This interpretation is consistent with findings obtained from the squid giant synapse (Llinás et al, 1981;Augustine et al, 1985;Augustine and Charlton, 1986) in which it is possible to correlate I C a and transmitter release at a high time resolution. It was shown that EPSC onsets were delayed when large presynaptic steps were applied or when external Ca 2ϩ concentration was decreased [see also results from the calyx of Held (Wu and Borst, 1999)].…”
Section: Changes In the Kinetics Of Transmitter Release During F2 Facsupporting
confidence: 80%
“…The cooperative action of three to five Ca 2ϩ ions acting on the Ca 2ϩ sensor(s) of the release machinery is believed to be required to trigger fusion of synaptic vesicles (Dodge and Rahamimoff, 1967;Augustine and Charlton, 1986;Stanley, 1986;Heidelberger et al, 1994;Bollmann et al, 2000;Schneggenburger and Neher, 2000). The requirement for simultaneous binding of multiple Ca 2ϩ ions constitutes a "biochemical cooperativity" (Dodge and Rahamimoff, 1967).…”
Section: Introductionmentioning
confidence: 99%